The biopolitics of intellectual property : regulating innovation and personhood in the information age / Gordon Hull. - Hull, Gordon, 1972- (Cambridge University Press, 2019)
As a central part of the regulation of contemporary economies, intellectual property (IP) is central to all aspects of our lives. It matters for the works we create, the brands we identify and the medicines we consume. But if IP is power, what kind of power is it, and what does it do? Building on the work of Michel Foucault, Gordon Hull examines different ways of understanding power in copyright, trademark and patent policy: as law, as promotion of public welfare, and as promotion of neoliberal privatization. He argues that intellectual property policy is moving toward neoliberalism, even as that move is broadly contested in everything from resistance movements to Supreme Court decisions. This work should be read by anyone interested in understanding why the struggle to conceptualize IP matters.